"I think we need to get a better generator": Household resilience to disruption to power supply during storm events. (May 2016) - Ghanem, Dana Abi; Mander, Sarah; Gough, Clair
Abstract: Electricity is becoming ever more central to the everyday practices of households. As the energy system decarbonises, it is likely that electricity will supply even more services, thereby increasing the dependence of communities on reliable electricity supply. In this situation, the risk of power outages during extreme weather events poses a serious challenge to the safety and wellbeing of communities. However, little is known of the capacity of households to manage normal day-to-day life in such circumstances. This paper focuses on the UK winter storms that occurred in February 2014, the result of which 80, 000 homes were left without power and communities not reconnected for several days. We outline the impacts these power outages had on households, describing the challenges faced and the strategies adopted to alleviate impacts. This provides insight into everyday household-level resilience achieved through social and material elements that constitute everyday life. Highlights: The resilience of UK householders to power cuts due to storms was explored. Resilience is achieved through modifying everyday electricity-related practices. DNO׳s should explore how to use community networks to communicate with households.